The Impact of Innovation on the Global Competitiveness of Polish Meat and Dairy Enterprises - Agnieszka Tul-Krzyszczuk; Paweł Jankowski (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The aim of the study was to analyse innovations implemented in the milk and meat industries, and their impact on increasing competitiveness. The study showed that the 2010-12 period saw the most product and process innovations being introduced. On the other hand, innovations in marketing were found to be more popular in 2013. Three groups of similar innovations were distinguished. The milk industry stood out when it comes to the extent of innovations implemented. Fewer innovations were found in the poultry meat industry. Beef and pork meat processing was the least innovative. The innovativeness of enterprises is greater with larger numbers of employees and the increase in scope of their field of operation. The implementation of innovations resulted in: improvement of the quality of goods (services), increase in stock, productive capabilities and revenues from sales, emergence of new markets, increase in competitiveness and prestige of the firm. Those are confirmed by the very good performance of foreign trade and better competitiveness rates of Polish meat producers.